2020
DOI: 10.3389/fvets.2020.00455
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Toxoplasmosis and Neosporosis in Water Buffalo (Bubalus bubalis)

Abstract: Toxoplasmosis and neosporosis are diseases with worldwide distribution that are associated with reproductive problems in livestock and responsible for economic losses. This review presents an overview of the current knowledge relative to these diseases in water buffalo (Bubalus bubalis). In general, buffalo are considered resistant to clinical toxoplasmosis because there are studies only reporting serological evidence of natural infection in these animals. Studies have described age, poor hygienic status of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…On the other hand, a strong association was found between the variable abortion and the seropositivity to T. gondii in goat and in water buffalo farms. The abortive role of Toxoplasma in small ruminants is widely recognized [23,24] whereas it is not common in cattle [34] and water buffaloes [35]. Recently, Ciuca et al [18] showed that the co-infection by Neospora caninum and T. gondii is significantly associated with abortion in a water buffalo farm located in the same area.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a strong association was found between the variable abortion and the seropositivity to T. gondii in goat and in water buffalo farms. The abortive role of Toxoplasma in small ruminants is widely recognized [23,24] whereas it is not common in cattle [34] and water buffaloes [35]. Recently, Ciuca et al [18] showed that the co-infection by Neospora caninum and T. gondii is significantly associated with abortion in a water buffalo farm located in the same area.…”
Section: Discussionmentioning
confidence: 99%
“…
The protozoan parasite Neospora caninum (N. caninum) is a Toxoplasma-like organism and the causative agent of neosporosis in animals. Subsequently, T. gondii and N. caninum are closely related apicomplexan parasites, sharing many morphological and biological features, (Sánchez-Sánchez et al, 2018) and are associated with reproductive problems in livestock (De Barros et al, 2020).
…”
mentioning
confidence: 99%
“…Toxoplasmosis is a cosmopolitan zoonotic disease caused by a protozoan parasite, Toxoplasma gondii (T. gondii) and it is of great concern for both animals and public health [3]. Subsequently, T. gondii and is closely related apicomplexan parasites, sharing many morphological and biological features, [1] and are associated with reproductive problems in livestock [4]. Domestic cats and other felids are definitive hosts of T. gondii, a large variety of mammals and birds that serve as intermediate hosts [5,6].…”
Section: Introductionmentioning
confidence: 99%